Understanding and protecting vulnerable financial consumers - Cartwright, Peter (Springer Verlag, 2015)
This article considers how consumer protection law and policy should address the interests of particularly vulnerable financial consumers. Specifically, the article proposes a taxonomy of vulnerability which helps to identify (a) what makes consumers particularly vulnerable, and (b) how consumer protection law and consumer policy (broadly understood) can respond to these causes in a way that provides such consumers with appropriate protection. Changes to economic conditions, legal requirements on traders and our understanding of consumer behaviour make discussion of these issues particularly topical. There is little doubt that finding solutions is extremely difficult. Trade-offs are necessary and some enduring factors that contribute to vulnerability, in particular poverty, sometimes appear intractable. Nevertheless, it is submitted that by identifying clearly both why consumers are vulnerable and how the factors that lead to such vulnerability can be addressed, it is possible to construct an environment which respects consumer choice while ensuring that the most vulnerable are protected appropriately.